A transvaginal removal and repair of vesicovaginal fistula due to mesh erosion - Vineet V Mishra; Tanvir Tanvir; Sumesh Choudhary; Nilesh Goraniya (Wolters Kluwer Medknow Publications, 2016)
Vesicovaginal fistula (VVF) is a devastating social problem. It can either result from obstetric trauma or following gynecological surgeries, malignancy, or radiation. We present a case of a 70-year-old woman who had a VVF following mesh augmentation surgery for anterior compartment prolapse. She required a transvaginal removal of the eroded mesh followed by a transvaginal repair of VVF using a Martius flap, 6 weeks later. Transvaginal removal of mesh is technically feasible and a good approach. Timing and route of surgery should be individualized.